Rest API Implementation on Presence System using QR-Code and Web-Based Haversine Formula Method - Yiyi, Supendi; Rasidin, .; Amelia Hani, . (INTI International University, 2023)
Student presence is one of the most important things in lecturing. However, the student attendance system at Langlangbuana University currently still uses a manual system in which students sign the attendance sheet provided. The attendance list system has several weaknesses, namely the vulnerability to the safekeeping of student attendance lists, loss or damage to the attendance sheet, and the use of a relatively long time so that the manual attendance process as a whole becomes inefficient. In order to minimize these weaknesses, we need a system that can process student attendance lists. There are technologies that can be used to reduce these cases, one of which is QRCode, which uses the REST API for the student attendance list system so that later students can carry out the attendance list process by scanning the QR code provided in the application. With this application, it will be easier for lecturers to manage attendance lists and for students to make attendance.